Detection and Identification of Oily Stain on Clothes in Sexual Assault Case: A Case Study (Indian Internet Journal of Forensic Medicine and Toxicology, 2013)
The presence of semen on the victim’s clothes may be suggestive of sexual intercourse by the accused with the victim, but the presence of some additional material along with semen stains becomes a vital clue in the sexual assault cases. The present communication deals with the detection and identification of the oily stain on the clothes.
Keywords: Oily stains; rape; oil in sexual assault